Pengetahuan Dan Rasionalitas Penggunaan Swamedikasi Masyarakat: Kajian Pada Masyarakat Kecamatan Sekupang Batam - Khairunnisa Khairunnisa (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2024)
Self-medication is the community's independent efforts to overcome diseases and symptoms before getting medical services. Irrational drug usage is common in its implementation due to the lack of public knowledge about rational medicine. This study aimed to measure the level of knowledge and rationality in self-medication in the community. This study was descriptive research using a cross-sectional survey method. Data was collected online using validated questionnaires. The knowledge and rationality questionnaires each had 10 questions, each respondent who answered correctly was scored 2 points, while those who answered incorrectly or did not know were scored 0.  Data was collected using the snowball sampling method. Data were analyzed descriptively to assess characteristics, knowledge and rationality. The chi-square test was used to assess the relationship between characteristics with knowledge and rationality.  A total of 375 respondents took part in the study. Most respondents had a moderate or fairly good level of knowledge (40.8%) and 68.5% of respondents had used self-medication rationally. The chi-square test showed that the last education affected knowledge and rationality of using self-medication, another factor that affected knowledge was a job. Knowledge did not significantly affect self-medication rationality. Knowledge about self-medication must be improved to increase public self-medication rationality.